2022
DOI: 10.3389/fmed.2021.781616
|View full text |Cite
|
Sign up to set email alerts
|

TLR4-Dependent DUOX2 Activation Triggered Oxidative Stress and Promoted HMGB1 Release in Dry Eye

Abstract: Dry eye disease (DED) is one of the most common ocular surface diseases worldwide. DED has been characterized by excessive accumulation of reactive oxygen species (ROS), following significant corneal epithelial cell death and ocular surface inflammation. However, the key regulatory factor remains unclear. In this study, we tended to explore whether DUOX2 contributed to DED development and the underlying mechanism. Human corneal epithelial (HCE) cells were treated with hyperosmolarity, C57BL/6 mice were injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Notably, HMGB1, an alternative ligand of the receptor for RAGE, and dual oxidase 2 (DUOX2), a subtype of NOX, play crucial roles in DED. Hyperosmolarity-induced DUOX2 activation, mediated by toll-like receptor 4 (TLR4)-dependent signaling and exacerbated by ROS excess, leads to HMGB1 release, cell death, and inflammation in a positive loop in human corneal epithelial cells exposed to DED conditions [136]. In a diabetic murine model, hyperglycemia induces a more severe mitochondrial bioenergetic deficiency in lacrimal gland cells compared to corneal cells.…”
Section: Diabetes-associated Dry Eye Disease Promotes Oxidatives Stre...mentioning
confidence: 99%
“…Notably, HMGB1, an alternative ligand of the receptor for RAGE, and dual oxidase 2 (DUOX2), a subtype of NOX, play crucial roles in DED. Hyperosmolarity-induced DUOX2 activation, mediated by toll-like receptor 4 (TLR4)-dependent signaling and exacerbated by ROS excess, leads to HMGB1 release, cell death, and inflammation in a positive loop in human corneal epithelial cells exposed to DED conditions [136]. In a diabetic murine model, hyperglycemia induces a more severe mitochondrial bioenergetic deficiency in lacrimal gland cells compared to corneal cells.…”
Section: Diabetes-associated Dry Eye Disease Promotes Oxidatives Stre...mentioning
confidence: 99%
“…ROS production has been detected in various models of in vitro studies [23,24]. RNA-seq analysis of corneal epithelial cells exposed to hyperosmolarity has revealed significant modulation in the activation of ROS metabolism processes [25]. In humans, numerous exogenous and endogenous factors are sources of ROS production, which was particularly emphasized in a recent cross-sectional study on population aging and lifestyle factors, where it was found that DED is associated with aging, reduced sleep duration, prolonged exposure to digital device screens, and increased psychological stress [26].…”
Section: Introductionmentioning
confidence: 99%
“…Following such recognition, PRRs lead to a microbe-free inflammatory response or a “sterile” inflammation. Thus, it has been determined that TF, in the case of DED, contains many of these alarmins, such as S100A4, S100A6, S100A8, S100A9, S100A11, and HMGB1 and many cytokines, which are accompanied by a recruitment of numerous immune cells in the ocular surface [ 5 , 6 , 7 , 8 ]. Moreover, regarding PRRs, they seem to have an increase of TLR expression and recruitment, such as TLR4 and TLR2, in surface epitheliums [ 9 , 10 , 11 , 12 ], with a particular emphasis on TLR4 implication in inflammation and on immune cell recruitment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This activation will induce cytokine expression and release and the attraction of immune cells to an inflammation site [ 18 , 19 , 20 ]. In dry eye syndrome, many potential RAGE ligands are released [ 5 , 6 , 7 ], but their involvement has not yet been studied at the ocular epithelium level. Thus, our study intends to provide new information about the molecular actors implicated in inflammation by focusing on the similarity/difference of response of surface epithelial cells (cornea and conjunctiva) in triggering the DED inflammation.…”
Section: Introductionmentioning
confidence: 99%